Public Budget Making in Nigeria: A Historical Analysis of its Legal Framework, 1954 – 1999 - OGUNYEMI, Adetunji Ojo (Ethiopian Journal of Social Sciences, 2018)
his study analyses the legal framework for the prudent management of Nigeria’s revenue and expenditure from 1954 up to 1999. It shows and discusses the constitutional and statutory provisions that were enacted for the dispensation and regulation of public finances particularly the federal budget, and how these provisions either changed or continued in the period. In addition, the paper analyses the significant provisions on prudence as they concern federal budget and the due process of public accountability in Nigeria especially since the consolidation of the country into a federation of multiple fiscal powers and responsibilities. The study concludes that constitutional laws on budgeting in Nigeria have always been sufficiently expressive on the requirements of the due process of financial planning and on the prohibition of corrupt acts and imprudent use of public resources; and that if the Nigerian financial system today is still bedevilled by misappropriation of those resources it will not be due to insufficient legal framework but the refusal to sanction its breach.